Intelligent Autonomous Decision-Making and Cooperative Control Technology of High-Speed Vehicle Swarms - Zhang, Dong; Huang, Wei (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a reprint of the Special Issue "Intelligent Autonomous Decision-Making and Cooperative Control Technology of High-Speed Vehicle Swarms",which was published in Applied Sciences.